Water‐Triggered Reconfigurable Glycerogels for Sustainable All‐Gel Supercapacitors - Md. Tariful Islam Mredha; Adith Varma Rama Varma; Tanish Gupta; Insu Jeon (Advanced Science)
Abstract The polymeric structures of synthetic gels are typically static, which makes them damage‐prone and nonrecyclable. Inspired by the dynamic reconfigurability of biological tissues, which eliminate old/damaged cells and regenerate new ones via biological triggers/signals, a reconfigurable biopolymer gel is presented based on a glycerol‐mediated supramolecular gelation strategy. In response to an eco‐friendly triggering agent water, this gel undergoes on‐demand molecular‐level reconfiguration. The versatility of the approach enables the development of reconfigurable gels with modulated functionality. As a proof‐of‐concept, a reconfigurable glycerogel electrode and electrolyte are developed and used to prototype an all‐gel supercapacitor that exhibits exceptional self‐healing, degradation, and rebuilding abilities. Furthermore, it can tolerate extreme mechanical deformations (e.g., stretching, bending, and twisting) and temperatures (−20 to 80 °C). The device exhibits excellent energy storage performance, with a maximum areal capacitance of 450 mF cm−2 (at 0.035 mA cm−2) and remarkable capacitance retention of 89% following 20 000 charge/discharge cycles (at 0.35 mA cm−2). Moreover, following self‐healing and rebuilding, the capacitance remains at 91% and 110% (at 0.35 mA cm−2) of the original value, respectively. This generalized strategy for preparing multifunctional reconfigurable gels will facilitate the development of high‐performance flexible and wearable devices with improved durability and recyclability.